Mechanisms and proteins involved in long-distance interactions - Georgiev, Pavel; Maksimenko, Oksana (Frontiers in Genetics, 2014)
Due to advances in genome-wide technologies, consistent distant interactions within chromosomes of higher eukaryotes have been revealed. In particular, it has been shown that enhancers can specifically and directly interact with promoters by looping out intervening sequences, which can be up to several hundred kilobases long. This review is focused on transcription factors that are supposed to be involved in long-range interactions. Available data are in agreement with the model that several known transcription factors and insulator proteins belong to an abundant but poorly studied class of proteins that are responsible for chromosomal architecture.